Grace and metaphysics in Maximus Confessor - Haynes, Daniel (2012)
Post-Tridentine Western Christian theology introduced the notion of natura pura, which holds that one can know created nature in fact without reference to God or divine grace. The orders of grace and nature are thus on different plains. This ontology creates an extrincism between God and the world. Maximus Confessor’s doctrine of grace offers the paradox of nature already presuming grace but awaiting the supernatural grace of deification at the resurrection. Further, divine grace, or energy in Maximus’s theology, are not separate ontological realms between God and the world. Grace does not separate God’s essence from his energies. The Incarnation of the created and uncreated natures in Christ fully manifests the paradox of God’s grace as being fully on the side of creation and on the side of God, without remainder. Finally, Maximus’s theurgic ecclesiology in his Mystagogy reinforces the mediation of grace through created reality. All of these aspects of Maximus the Confessor’s theology of grace provide a Christian rendering of participation that does not result in the extrincism of grace from nature, their conflation together, or a real distinction in the being of God.